Teacher Voice from Digital Screens: Perception Analysis and Readiness for Online Clinical Supervision - Febi Febrianto; Muthi'ah Rahman; Rifka Jannatul Firdausiyah; Uryatul Hikmah; Robert Edy Sudarwan (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
This study aims to analyze teacher perception, teacher readiness, as well as supporting and inhibiting factors in the implementation of online clinical supervision at MTs Hikmatul Hasanah. The research uses a qualitative approach with a case study design. Data were collected through observation and semi-structured interviews involving madrasah heads, madrasah deputy heads for curriculum, academic supervisors, and teachers who had participated in online clinical supervision. Data analysis is carried out through the process of data condensation, data reduction, data presentation, and data verification by utilizing content analysis, discourse analysis, and interpretive analysis. The results of the study showed that teachers have a positive perception of online clinical supervision because it provides ease of communication, time flexibility, efficiency of implementation, and ease of documentation of supervision results. Teachers' readiness in facing digital-based supervision is in the category of being quite good, which is shown by the ability to use supervision support technology, openness to feedback, and willingness to adapt to change. Supporting factors for the implementation of online clinical supervision include madrasah policy support, technology training, mentoring, availability of digital facilities, and good communication between supervisors and teachers. The inhibiting factors include limited internet networks, differences in digital competencies, limitations in technological devices, and reduced intensity of face-to-face interactions. The findings of the study show that teachers' positive perceptions correlate with increased readiness to participate in digital-based clinical supervision. Therefore, the success of online clinical supervision requires adequate technological support, strengthening digital competencies, and communicative and reflective professional relationships.